Peningkatkan Keaktifan Dan Hasil Belajar Fisika Melalui Permainan Puzzle Berkelompok Pada Materi Kalor - Kristina Suprapti (PGSD Universitas Muria Kudus, 2022)
This study aims to increase the activeness and learning outcomes of Physics through group puzzle games in class XI MIPA 1 students of SMA Negeri 1 Rembang. This research is a classroom action research that will be carried out in August 2022. The subjects of this research were 36 students in class XI MIPA 1 at SMA Negeri 1 Rembang. This classroom action research was conducted in 2 cycles and each cycle consisted of 4 stages, namely planning, implementing, observing, and reflecting. Data collection techniques in this study used test and non-test techniques. The test instrument is in the form of evaluation questions, while the non-test instrument is in the form of student activity observation sheets. Data were analyzed using quantitative descriptive techniques.The results showed that there was an increase in learning outcomes with the application of group puzzle games. The average score of students in pre-cycle was 63.64, increasing to 85.11 in cycle 1 and 87.75 in cycle 2. Student activity also increased from inactive pre-cycle conditions to students being actively involved in learning activities. This is because there are media used in the learning process that help students discuss each other in groups to better understand the concept of heat transfer.